Critical Discourse Analysis of Ambonese Pop Songs - Prasojo Yekti Perdana (Jurnal Pengetahuan dan Pendidikan, 2025)
This qualitative study analyzes the content of five Ambonese pop songs to explore themes of criticism, freedom of life, love betrayal, and self-determination, and to understand the use of translingualism in music. The research employs directed content analysis, drawing on existing theories and hypotheses to guide the analysis. The samples in the study are five Ambonese pop songs: "Hela Napas," "YOLO," "Iris," "Se Dimana," and "Better Know." The songs were chosen for their use of mixed languages (Ambon-Malay, Bahasa Indonesia, and English) and their thematic relevance. Data was collected through the examination of song lyrics and interviews with the songwriters to gain insight into their perspectives. The analysis process involved coding the data into categories and themes, followed by thematic analysis. The findings reveal the richness of language use in conveying societal critiques, personal experiences, and cultural pride. Grizzly's songs serve as a powerful medium for social commentary, urging listeners to pursue their dreams, cherish relationships, and respect themselves and others. The study sheds light on the cultural and social context of Eastern Indonesia, providing insights into the way language is utilized in music to express emotions, ideologies, and identity